Reseñas Víctor Manuel. La caída del último higuerón. San José: Editorial Lunes, 2007 - González Calvo, Mainor (Universidad de Costa Rica, 2011)
Reseñas Víctor Manuel. La caída del último higuerón. San José: Editorial Lunes, 2007